2013
DOI: 10.1186/2251-712x-9-37
|View full text |Cite
|
Sign up to set email alerts
|

Process capability improvement of an engine connecting rod machining process

Abstract: Statistical process control is an excellent quality assurance tool to improve the quality of manufacture and ultimately scores on end-customer satisfaction. SPC uses process monitoring charts to record the key quality characteristics (KQCs) of the component in manufacture. This paper elaborates on one such KQC of the manufacturing of a connecting rod of an internal combustion engine. Here the journey to attain the process potential capability index (C p ) and the process performance capability index (C pk ) va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The Post-hoc test establishes the extent of influence of the causes on the CTQ characteristic of concern. In connecting rod and crankshaft components of engine manufacturing, ANOVA is successfully employed for identifying the major root causes and subsequently for identifying the extent of influence of these root causes on process deviations [11,12]. Among the varied areas of applications of ANOVA, one such area is manufacturing of shafts used in submersible pumps [13].…”
Section: Anova (Analysis Of Variance)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Post-hoc test establishes the extent of influence of the causes on the CTQ characteristic of concern. In connecting rod and crankshaft components of engine manufacturing, ANOVA is successfully employed for identifying the major root causes and subsequently for identifying the extent of influence of these root causes on process deviations [11,12]. Among the varied areas of applications of ANOVA, one such area is manufacturing of shafts used in submersible pumps [13].…”
Section: Anova (Analysis Of Variance)mentioning
confidence: 99%
“…Remedial actions are taken to correct and prevent variations in the process. Another noted area of application of FMEA is the engine manufacturing process [11,12]. In the area of engine manufacturing, FMEA is carried out for the Failure Modes of the following observed CTQ characteristics namely, thrust face width of connecting rod and crankshaft stub-end hole diameter after boring operation.…”
Section: Fmea (Failure Modes and Effects Analysis)mentioning
confidence: 99%
“…India is the largest milk producer in the world (about 100 million MT) and consists of nearly 1/5th of the world bovine population (Deloitte 2009). Further, (Sharma and Rao 2013) revealed that the DMAIC approach is the best methodology for problem solving tools to improve the manufacturing process capability levels.…”
Section: Introductionmentioning
confidence: 99%
“…Boyles (1994) proposed S pk index based on the process yield of the process. Sharma and Rao (2013) employed define, measure, analysis, improvement and control (DMAIC) approach to reduce the variation of the engine connecting rod machining process and as a result to improve the capability of the process. Also, Sharma and Rao (2014) used DMAIC approach to improve the capability of the engine crankshaft manufacturing process.…”
Section: Introductionmentioning
confidence: 99%